Vegetation Quality Assessment of the Shaanxi Section of the Yellow River Basin Based on NDVI and Rain-Use Efficiency - Zhao Liu; Danyue Wang; Lei Han; Hongliang Kang; Xinxin Cao (Land)
The Yellow River Basin is a critical region for ecological environment protection and social and economic development in China. It is of great significance to study vegetation dynamics for the high-quality development of the Yellow River Basin. In this study, based on the data of NDVI and precipitation datasets in the growing season (June to September) from 2000 to 2019, we used a Sen+Mann–Kendall trend analysis and other methods to study the spatial and temporal evolution characteristics of precipitation and vegetation cover in the Shaanxi section of the Yellow River Basin and to assess the regional vegetation quality change characteristics based on estimating the rain-use efficiency (RUE). The results show the following: (1) The precipitation in the study area showed a spatial distribution pattern of more in the south and less in the north, in which Yulin City had the lowest precipitation overall, but it was an area with significant increasing precipitation. (2) The NDVI value of the Shaanxi section of the Yellow River Basin showed an overall upward trend from 2000 to 2019, with a growth rate of 0.327/10a. The vegetation cover showed the spatial characteristics of high in the south and low in the north, which showed that the vegetation growth condition was poor in the wind-sand grassland area at the southern edge of the Mu Us Sandland in the northwestern part of Yulin City and the construction areas in the Guanzhong Plain. Meanwhile, the vegetation grew well in Yan’an City and the area close to the Qinba Mountains. Moreover, the NDVI of the study area increased with the increase in precipitation. (3) The vegetation quality in the study area showed fluctuating interannual changes and a weak upward trend. More than 80% of the vegetation in the study area was in a state of improvement, and the areas with more significant improvement were mainly located in the northern part of the study area, while the vegetation was degraded in the urban and urban suburb areas in the Guanzhong Plain. The results of this study are of great practical significance for promoting the socio-economic development of the Yellow River Basin in coordination with ecological environmental protection.